Marine microbial community responses related to wetland carbon mobilization in the coastal zone. Issue 1 (3rd December 2018) - Ward, Nicholas D.; Morrison, Elise S.; Liu, Yina; Rivas‐Ubach, Albert; Osborne, Todd Z.; Ogram, Andrew V.; Bianchi, Thomas S.
Abstract: Here, we examine how marine microbial communities respond when dissolved organic matter (DOM) is mobilized from coastal wetlands. Biological transformations of this DOM may increase in the presence of reactive substrates, such as algal‐derived DOM (ADOM) in the coastal zone—a process known as priming. We performed laboratory experiments examining transformations of DOM derived from coastal wetland peat (PDOM) with and without the presence ADOM. Associated shifts in microbial community composition and functional gene abundance were measured to evaluate mechanisms of priming effects. ADOM presence stimulated CO2 production when compared to the seawater control, which was further enhanced in the copresence of PDOM. DOM characterization showed a substantial difference in features present at the end of the incubation when PDOM was present with and without ADOM, while metagenomic sequencing indicated shifts in microbial community composition and identified 23 unique functional genes associated with pathways for the breakdown of aromatic compounds.